2022
DOI: 10.1021/acs.molpharmaceut.2c00738
|View full text |Cite
|
Sign up to set email alerts
|

Poly(aspartic acid)-Based Polymeric Nanoparticle for Local and Systemic mRNA Delivery

Abstract: Recently, therapeutics based on mRNA (mRNA) have attracted significant interest for vaccines, cancer immunotherapy, and gene editing. However, the lack of biocompatible vehicles capable of delivering mRNA to the target tissue and efficiently expressing the encoded proteins impedes the development of mRNA-based therapies for a variety of diseases. Herein, we report mRNA-loaded polymeric nanoparticles based on diethylenetriamine-substituted poly­(aspartic acid) that induce protein expression in the lungs and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Our work indicated that VLSs were capable of not only transfecting 293 encoding GFP or the S1 protein, was expressed dynamically in local tissue (Supplementary Fig. 4), similar to what has been reported for mRNA vaccines 20 . Interestingly, the rate of S1 antigen colocalization with DCs or macrophages in local tissue in mice in the VLS group was greater than that in mice in the mRNA-or protein-alone groups (Fig.…”
Section: Vlss Enable Cell Transfection and Target Ace2/dc-sign Moleculessupporting
confidence: 84%
“…Our work indicated that VLSs were capable of not only transfecting 293 encoding GFP or the S1 protein, was expressed dynamically in local tissue (Supplementary Fig. 4), similar to what has been reported for mRNA vaccines 20 . Interestingly, the rate of S1 antigen colocalization with DCs or macrophages in local tissue in mice in the VLS group was greater than that in mice in the mRNA-or protein-alone groups (Fig.…”
Section: Vlss Enable Cell Transfection and Target Ace2/dc-sign Moleculessupporting
confidence: 84%
“…Intravenous injection of PEGylated poly(aspartic acid) could achieve pulmonary targeted mRNA transfection with increased cell viability compared to non‐PEGylated nanoparticles. [ 82 ] This PEGylated poly(aspartic acid) nanoparticle could be a potential lung‐targeted therapy for the local disease.…”
Section: Materials Development For Nucleic Acid Pulmonary Deliverymentioning
confidence: 99%
“…Yum et al [ 175 ] synthesized PASP (DET/CHE) with a cyclohexyl ethyl (CHE) group, which caused significant mRNA expression in the lungs and even demonstrated mRNA transfection efficiency nearly 10 times higher than lipid materials commonly used on the market. Park et al [ 176 ] found that PEG-modified PASP (DET) (with a PEG/polymer ratio of 1:1) can induce mRNA expression in the lungs, but caution should be exercised as high PEG content may decrease the efficiency of mRNA delivery after intravenous injection. mRNA transduction and translation in the lungs were completely absent when the PEG/polymer ratio was 10:1.…”
Section: Mrna Nps: Targeting Design Strategies For Different Tissuesmentioning
confidence: 99%